Apnea after Awake Regional and General Anesthesia in Infants: The General Anesthesia Compared to Spinal Anesthesia Study—Comparing Apnea and Neurodevelopmental Outcomes, a Randomized Controlled Trial. (July 2015) - Davidson, Andrew J.; Morton, Neil S.; Arnup, Sarah J.; de Graaff, Jurgen C.; Disma, Nicola; Withington, Davinia E.; Frawley, Geoff; Hunt, Rodney W.; Hardy, Pollyanna; Khotcholava, Magda; von Ungern Sternberg, Britta S.; Wilton, Niall; et al.
Abstract : Background: Postoperative apnea is a complication in young infants. Awake regional anesthesia (RA) may reduce the risk; however, the evidence is weak. The General Anesthesia compared to Spinal anesthesia study is a randomized, controlled trial designed to assess the influence of general anesthesia (GA) on neurodevelopment. A secondary aim is to compare rates of apnea after anesthesia. Methods: Infants aged 60 weeks or younger, postmenstrual age scheduled for inguinal herniorrhaphy, were randomized to RA or GA. Exclusion criteria included risk factors for adverse neurodevelopmental outcome and infants born less than 26 weeks gestation. The primary outcome of this analysis was any observed apnea up to 12 h postoperatively. Apnea assessment was unblinded. Results: Three hundred sixty-three patients were assigned to RA and 359 to GA. Overall, the incidence of apnea (0 to 12 h) was similar between arms (3% in RA and 4% in GA arms; odds ratio [OR], 0.63; 95% CI, 0.31 to 1.30, P = 0.2133); however, the incidence of early apnea (0 to 30 min) was lower in the RA arm (1 vs. 3%; OR, 0.20; 95% CI, 0.05 to 0.91; P = 0.0367). The incidence of late apnea (30 min to 12 h) was 2% in both RA and GA arms (OR, 1.17; 95% CI, 0.41 to 3.33; P = 0.7688). The strongest predictor of apnea was prematurity (OR, 21.87; 95% CI, 4.38 to 109.24), and 96% of infants with apnea were premature. Conclusions: RA in infants undergoing inguinal herniorrhaphy reduces apnea in the early postoperative period. Cardiorespiratory monitoring should be used for all ex-premature infants. Abstract : In a secondary analysis of more than 700 infants more than 60 weeks postmenstrual age randomized to regional or general anesthesia for inguinal herniorrhaphy, there was no difference in the incidence apnea in the first 12 postoperative hours (primary outcome measure), although early apnea in the first 30 min was less with regional.